2002
DOI: 10.1111/1475-3995.00387
|View full text |Cite
|
Sign up to set email alerts
|

A note on the NP–hardness of the consecutive block minimization problem

Abstract: We show that consecutive block minimization problem is NP-hard even when restricted to binary matrices that have two ones per row.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 3 publications
0
14
0
Order By: Relevance
“…Thus, solving CBM is equivalent to minimizing the number of holes. CBM is NP-hard even when restricted to binary matrices having two 1s per row (Haddadi 2002). Haddadi and Layouni (2008) converted CBM to traveling salesman problem (TSP) satisfying the triangle inequality.…”
Section: Preprocessingmentioning
confidence: 99%
“…Thus, solving CBM is equivalent to minimizing the number of holes. CBM is NP-hard even when restricted to binary matrices having two 1s per row (Haddadi 2002). Haddadi and Layouni (2008) converted CBM to traveling salesman problem (TSP) satisfying the triangle inequality.…”
Section: Preprocessingmentioning
confidence: 99%
“…The first node corresponding to each item is pointed from a header table and each FP Tree node contains a link to the next node corresponding to the same item. Table 1, each node contains an item:frequency pair, and dotted arrows represent node links Example 1: Considering the transaction database in Table 1, the FList contains items in the order (3,2,4,5,1). Column 3 of Table 1 presents items in each transaction ordered according to the FList, and Figure 1 presents the corresponding FP Tree.…”
Section: Trie-based Representationsmentioning
confidence: 99%
“…Counting the number of 1-bits, we obtain the itemset support count of 2. The resulting bit vector also identifies the transactions (i.e., 4,6) that contain the query itemset.…”
Section: Bitmap-based Representationsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that deciding if the columns of M can be ordered in such a way that every row contains at most k contigs is NP-complete even if k = 2 [2]. Also finding an ordering of the columns that minimizes the number of gaps in M is NP-complete even if each row of M has at most two ones [3].…”
Section: Introductionmentioning
confidence: 99%